Major depressive disorder with unusual symptoms in a school going child - Bainade, Kapil; Kotrashetti, Veeranna; Elon, Neelu; Bhattacharjee, Arnab (International Journal of Contemporary Pediatrics, 2025)
Major depressive disorder is an important public health concern. Early childhood onset of depression can be severe and may lead to grave consequences. Now-a-days major depression disorder is one of the most common psychiatric disorders in children but due to the variation in clinical presentations, it often not recognized and goes untreated. Owing to difficult and unusual presentations, the diagnosis as well as management of childhood onset depression is very challenging. Here we will discuss about a case of an 8-year-old school going boy with atypical symptoms of severe headache and body ache, which was later diagnosed as major depressive disorder by using DSM-5 criteria after taking detailed history from parents, family members and performing repeated mental state examination and closely observing his activities in ward. Due to vast varieties in clinical symptoms, it is often difficult to diagnose at an early stage and it goes highly underreported and undetected which in future can lead to severe and grievous mental and physical health issue.